Efforts of Counseling Teacher in Overcoming Student Tuning Behavior at MTS Negeri 1 School Deli Serdang - Bagus Setiawan; Nurussakinah Daulay (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to determine the efforts of Counseling Guidance teachers in overcoming the behavior of students who play true, because there are still many students who often play true as seen by us at this time, there are those who participate in promiscuity, are lazy to study and others. Of course, in this study, researchers discussed how the counseling teacher's efforts to overcome the behavior of students who skipped school in an effective way carried out by the counseling teacher. This research leads to a qualitative descriptive research method, the data of which was taken from interviews with 2 existing sources. And the results of this study were: According to all informants, it was concluded that the counseling teacher's efforts to deal with students who skipped school were to approach the counseling teacher to students and provide a service with group counseling services and group guidance.